Grinding patterns in migraine patients with sleep bruxism: a case-controlled study. Issue 6 (1st November 2016) - Kato, Momoko; Saruta, Juri; Takeuchi, Mifumi; Sugimoto, Masahiro; Kamata, Yohei; Shimizu, Tomoko; To, Masahiro; Fuchida, Shinya; Igarashi, Hisaka; Kawata, Toshitsugu; Tsukinoki, Keiichi
Abstract : Objectives: Details on grinding patterns and types of contact during sleep bruxism in association with migraine headache have not yet been elucidated. This study compared the characteristics of sleep bruxism between patients with migraine and controls. Methods: The study included 80 female patients who had been diagnosed with migraine and 52 women with no history of migraine. Grinding patterns were measured using the BruxChecker® (Scheu Dental, Iserlohn, Germany). Results: There was a significant difference between the two groups in the distribution of grinding patterns at the laterotrusive side ( p < 0.001). When the anterior teeth and premolar and molar regions in the two groups were compared, the proportion of the grinding area at all sites was significantly larger in the migraine group than in the control group ( p < 0.001). Discussion: The BruxChecker® showed that there was substantial grinding over a large area among migraine patients, particularly in the molar region.